Linking rehabilitation and re-integration process to examine re-offending behaviour - Lee, Kit Ying (2019)
Risk-Need-Responsitivity (RNR) framework is one of the most widely applied framework in correctional rehabilitation. It is common for offenders to present multiple needs for intervention, however, RNR framework provide little guidance on the design for intervention programs in such cases. Especially for drug offenders, the well-documented relationship between drug and crime suggest inter-play between drug abuse and criminal thinking. Apart from the drug-crime nexus, familial relationship supports the rehabilitation journey for drug offenders. The current study examined whether change via an intervention that targets the three areas could be related. Secondary data from 327 male inmates above the age of 18, incarcerated due to drug-related offence was used. The data was collected as part of a larger evaluation study on interventions for drug offenders by Singapore Prison Service. The results suggested that better familial relationship at pre-intervention could increase the rate of change for criminal thinking and drug abuse. Rate of change in criminal thinking and drug abuse were positively correlated, suggesting that the two needs could be targeted together.